2009
DOI: 10.1002/ijc.24419
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin targets Akt‐mediated prosurvival signaling in human breast cancer cells

Abstract: In recent years, Akt signaling has gained recognition for its functional role in more aggressive, therapy‐resistant malignancies. As it is frequently constitutively active in cancer cells, several drugs are being investigated for their ability to inhibit Akt signaling. The purpose of this study is to determine effect of diosgenin (fenugreek), a dietary compound on Akt signaling and its downstream targets on estrogen receptor positive (ER+) and estrogen receptor negative (ER−) breast cancer (BCa) cells. Diosgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 41 publications
8
105
0
Order By: Relevance
“…XIAP has been shown to interact with and inhibit caspase-3 activity (23). Recently it has been reported that the expression of p-AKT and XIAP are closely related and Akt is constitutively active in HCT-116 cells (12,14). In this study, we found AIMs could induce caspase-3 activity and the subsequent cleavage of caspase-3 substrate PARP by suppression of XIAP probably through suppression of p-Akt.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…XIAP has been shown to interact with and inhibit caspase-3 activity (23). Recently it has been reported that the expression of p-AKT and XIAP are closely related and Akt is constitutively active in HCT-116 cells (12,14). In this study, we found AIMs could induce caspase-3 activity and the subsequent cleavage of caspase-3 substrate PARP by suppression of XIAP probably through suppression of p-Akt.…”
Section: Discussionsupporting
confidence: 48%
“…p-Akt is an important factor regulating the expression of several pro-apoptotic or anti-apoptotic proteins (13)(14)(15)(16). XIAP has been shown to interact with and inhibit caspase-3 activity (23).…”
Section: Discussionmentioning
confidence: 99%
“…[9] It was also revealed that the low solubility of DG led to poor bioavailability and gastrointestinal mucosal toxicity. [10] As poor solubility has been recognized as a frequently encountered challenge in the field of pharmaceutics, different approaches have been employed to improve the solubility and bioavailability of poorly watersoluble compounds including DG. [11] For instance, an inclusion of complexation of DG and β-cyclodextrin was formed.…”
Section: Introductionmentioning
confidence: 99%
“…McAnuff (2005) Inhibition of glucose-uptake and glucagon-induced hepatic glycogen phosphorylase A activity in vitro Al-habori (2001) Anticoagulant activity, inhibition of platelet aggregation and thrombosis in vivo Gong (2011) Decrease of plasma total cholesterol and LDL-cholesterol, increase of HDL-cholesterol and total cholesterol ratio in rats Xu et al (2009) Enhancement of BK (Ca)-channel activity in human cortical neurons Wu (2006) Decrease of blood pressure, oxidative stress and cardiac remodeling in the heart of adenine-induced chronic renal failure rats Manivannan (2015) Increase of antioxidant level, decrease of ACE activity, lipid peroxidation level and cardiac fibrosis in chronic renal failure rats Manivannan (2015) Inhibition of platelet aggregation and acetylcholinesterase activity Sautour (2004) Decrease of serum total cholesterol levels in rats Ghayur ( Inhibition of tumor growth in MCF-7 and MDA-231 xenografts in nude mice Lepage et al (2011) Inhibition of melanogenesis by activating the PI3K pathway Srinivasan et al (2009) Apoptosis induction and growth inhibition of HCT-116 human colon carcinoma cells Lee et al (2007) Apoptosis induction and downregulation of COX-2 expression and activity in human rheumatoid synovial cells Raju and Bird (2007) Inhibition of viability and proliferation of breast cancer cells Liagre et al (2007) Osteoclastogenesis suppression by inhibiting NF-kappaB-regulated gene expression Li et al (2005) Growth inhibition and apoptosis induction in HT-29 human colon cancer cells Shishodia and Aggarwal (2006) p53 activation and cell cycle arrest in the different cell lines Raju et al (2004) Anticancer activity on S-180, HepA, U14 transplant mice and L929, HeLa, MCF cells Corbiere et al (2004) Normalization of lipid levels by excretion through faeces in diabetic rats Wang et al (2002) progesterone from diosgenin at Parke-Davis Pharmaceutical Company, in 1940. Progesterone is produced in various formulations by many pharmaceutical companies for hormone replacement therapy during menopause.…”
Section: Diosgeninmentioning
confidence: 99%